2
$\begingroup$

This is how I'm trying to integrate this function:

\begin{align*} \int \sqrt{3-2x-x^2}\, dx &= \int \sqrt{4-(x+1)^2}\, dx \\ &= \int \sqrt{2^2-(x+1)^2}\, dx \end{align*} Here I make the substitution:

$$ u=x+1 $$ $$du=dx$$

So the integral is now:

$$ \int \sqrt{2^2-u^2}\, du $$

I make a trigonometric substitution thinking about a right triangle where the hypothenuse is $2$, the adjacent side is $u$, the opposite side is $\sqrt{2^2-u^2}$, and the angle is called $\theta$.

$$ \sin(\theta)= \frac{\sqrt{2^2-u^2}}{ 2}$$ $$\bbox[2px,border:2px solid red] { 2\sin(\theta)= \sqrt{2^2-u^2}\qquad }$$

$$\frac{u}{2} =\cos(\theta)$$ $$ u=2 \cos(\theta)$$ $$ \bbox[2px,border:2px solid red] {du=-2 \sin(\theta)\,d\theta\qquad }$$

So I write the integral as: \begin{align*} \int 2\sin(\theta)(-2)\sin(\theta)\,d\theta &= \int (-4)\sin(\theta)\sin(\theta)\,d\theta \\ &= \int (-4){\sin}^2(\theta)\,d\theta \\ &= (-4)\int {\sin}^2(\theta)\,d\theta \\ &= (-4)\int \frac{1}{2}(1-\cos(2\theta))\,d\theta \\ &= (-4)\frac{1}{2}\int (1-\cos(2\theta))\,d\theta \\ &= (-2)\int (1-cos(2\theta))\,d\theta \\ &= (-2)\left[\int d\theta-\int \cos(2\theta)\,d\theta \right]\\ &= (-2)\left[\theta-\int \cos(2\theta)\,d\theta \right]\\ &= (-2)\left[\theta-\frac{1}{2} \sin(2\theta) \right]\\ &= \sin(2\theta) -2\theta \end{align*} And since $\cos(\theta) = u/2$, I know that $\theta =\arccos(u/2)$.

Therefore I have:

$$ \sin(2\arccos(u/2)) -2\arccos(u/2)$$

According to my first substitution $u=x+1$ so the final result is:

$$\bbox[2px,border:2px solid red] {\sin\left(2\arccos\left(\frac{x+1}{2}\right)\right) -2\arccos\left(\frac{x+1}{2}\right) + constant }\qquad$$

Can anyone help me? I don't understand what I'm doing wrong. Thanks!

$\endgroup$
  • 1
    $\begingroup$ Why do you think your answer is wrong? $\endgroup$ – B. Goddard Sep 15 '16 at 22:54
3
$\begingroup$

Answer is correct, if you want it to match with one that Wolfram produce, there should be done following: $$ \sin(2\theta)=2\sin(\theta)\cos(\theta)=2\frac{1}{2}\sqrt{2^2-u^2}\frac{u}{2}=\frac{u}{2}\sqrt{4-u^2}\\ u\to x+1\\ \sin(2\theta)=\frac{1}{2}(x+1)\sqrt{3-2x-x^2} $$ And for second addendum $$ \arccos(u/2)=\frac{\pi}{2}-\arcsin(u/2)\\ 2\arccos(u/2)=\pi-2\arcsin\left(\frac{x+1}{2}\right) $$ Altogether (hiding $\pi/2$ in constant): $$ \int \sqrt{3-2x-x^2} dx = \frac{1}{2}(x+1)\sqrt{3-2x-x^2}+2\arcsin\left(\frac{x+1}{2}\right)+const $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.